Saline versus albumin fluid for extracorporeal removal with slow low-efficiency dialysis (SAFER-SLED): study protocol for a pilot trial - Clark, Edward G; McIntyre, Lauralyn; Ramsay, Tim; Tinmouth, Alan; Knoll, Greg; Brown, Pierre-Antoine; Watpool, Irene; Porteous, Rebecca; Montroy, Kaitlyn; Harris, Sophie; Kong, Jennifer; Hiremath, Swapnil (Université d'Ottawa | University of Ottawa, 2019)
Abstract Background Critically ill patients frequently develop acute kidney injury that necessitates renal replacement therapy (RRT). At some centers, critically ill patients who are hemodynamically unstable and require RRT are treated with slow low-efficiency dialysis (SLED). Unfortunately, hypotension is a frequent complication that occurs during SLED treatments and may limit the recovery of kidney function. Hypotension may also limit the amount of fluid that can be removed by ultrafiltration with SLED. Fluid overload can be exacerbated as a consequence, and fluid overload is associated with increased mortality. Occasionally, intravenous albumin fluid is given to prevent or treat low blood pressure during SLED. The intent of doing so is to increase the colloid oncotic pressure in the circulation to draw in extravascular fluid, increase the blood pressure, and enable more aggressive fluid removal with ultrafiltration. Nonetheless, there is little evidence to support this practice and theoretical reasons why it may not be especially effective at augmenting fluid removal in critically ill patients. At the same time, albumin fluid is expensive. As such, we present a protocol for a study to assess the feasibility of a randomized controlled trial evaluating the use of albumin fluid versus saline in critically ill patients receiving SLED. Methods This study is a single-center, double-blind, and randomized controlled pilot trial with two parallel arms. It involves randomly assigning patients receiving SLED treatment in the ICU to receive either albumin (25%) boluses or normal saline fluid boluses (placebo) to prevent and treat low blood pressure. Discussion The results of this pilot trial will help with planning a larger trial comparing the efficacy of the interventions in achieving fluid removal in critically ill patients with AKI on SLED. They will establish whether enough participants would participate in a larger study and accept the study procedures. Trial registration This trial is registered on ClinicalTrials.gov Identifier NCT03665311 , registered on September 11, 2018.